Desain dan Proses Manufaktur Prototipe Mesin Pengupas, Pemotong, dan Penggiling Bawang Merah Model Portabel - Ulum, Miftahul; Pratama, Febriansyah Sukma; Putra, Arrizal Eka; Syarifuddin, Imam; Sugiono, Didik (Universitas Muhammadiyah Yogyakarta, 2023)
Onions undergo the processes of peeling and cutting. Home industries still use different types of independent peeling and cutting machines. In this study, a peeling, cutting, and grinding machine were designed using an adjustable peeling tube for peeling or direct cutting needs. The method used to obtain the cost of production was by analyzing the calculation of the manufacturing process, including the calculation of the component manufacturing process. The results of planning and calculating showed that the peeling force was 2.49 kgf, while the cutting force was 1.8 kgf. At a planned rotation of 700 rpm, the motor power became 117 W, so a motor with a power of 0.25 HP was used. The experiment using 1 kg of onions, the peeling time reached about 3.5 minutes and the cutting time was 20 seconds. The total machining process time gained 42.17 hours, the total machining process costs earned IDR 1,328.141, the total purchase of materials was IDR 5,220,000, and the total production cost reached IDR 6,548,141.